Langerin, the “Catcher in the Rye”: An important receptor for pathogens on Langerhans cells - Stoitzner, Patrizia (Eur J Immunol, 2011)
Langerhans cells (LCs) are a distinct subset of DCs that resides in the epidermis and other epithelia. They are potent antigen-presenting cells and strong inducers of T-cell responses. Like other DC types, LCs express C-type lectins that serve as antigen/pathogen uptake receptors, with Langerin/CD207 being the characteristic LC C-type lectin. In this issue of the European Journal of Immunology, Geijtenbeek and colleagues [Eur. J. Immunol. 2011. 41: 2619–2631] assign a role to Langerin on human LCs for binding and capturing measles virus. Interestingly, however, this function does not correlate with productive infection or with cross-presentation of measles virus. These authors show that measles virus does not infect the LCs via Langerin, and that LCs cannot cross-present the virus to CD8(+) T cells; however, presentation of this virus to CD4(+) T cells occurs and is dependent on virus capture by Langerin. Thus, cross-presentation of measles virus may be left to skin DCs other than LCs. This highlights the complexity of anti-viral T-cell responses that originate in the skin and also emphasizes the need for intensified investigations into human skin DCs in order to be able to ultimately harness their potential for immunotherapy.